PENETAPAN PEMBULATAN HARGA DAN NILAI TIMBANGAN PADA JASA EKSPEDISI J&T EXPRESS CABANG KANDANGAN - Fadia Fitriani; Norwilistini (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2024)
Online shopping and selling, which is associated with community-beneficial products delivery services, is an example of how people's inherent need for the easy and practical drives this study. J&T Express is one of the many businesses and individuals that rely on for delivery services. Finding out how the J&T Express Kandangan branch rounds prices and weighs them was the driving force behind this research. A qualitative approach was utilised in this investigation. Observation, interviews, and documentation are the methods used to gather data. Facts gleaned from interviews with J&T Express Kandangan branch workers and customers show that the company's practice of rounding pricing and scales goes against what the Qur'an says, Surah Hud verse 85, which in this verse commands to fulfill/perfect measurements and scales fairly and not to harm the rights of others.